Association of Carney Complex with an Intronic Splice Site Mutation in the PRKAR1A Gene - Guo, H.; Xiong, H.; Li, Z.; Xu, J.; Zhang, H.; Chen, X.; Hu, S. (Hormone and Metabolic Research, 2016)
This study was aimed to investigate the clinical features and mutations in the PRKAR1A gene of a multigenerational kindred including 17 individuals at risk for Carney complex. Eight patients were diagnosed with Carney complex among the 17 individuals (47.1%). Among the 8 affected patients, 4 had cardiac myxomas, 8 had skin pigmentation, and 3 had diabetes. Genomic DNA sequencing in 14 surviving patients showed 6 had the same germline mutation in the sixth intron and affected the splice site. cDNA sequencing and DNAMAN software showed 159 bases were absent, resulting in the absence of the amino acids 249 to 301 from the protein. All 6 patients with this PRKAR1A gene mutation had skin pigmentation. In conclusion, the present study reported for the first time an intronic splice site mutation in the PRKAR1A gene of a Chinese family with Carney complex, which probably caused skin pigmentation observed in affected family members.
Keywords: Carney complex; PRKAR1A gene; intron; mutation; myxomas